2020
DOI: 10.1038/s41598-020-63030-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic factors in elbow tendon pathology: a case-control study

Abstract: Elbow tendinopathy is a common pathology of the upper extremity that impacts both athletes and workers. Some research has examined the genetic component as a risk factor for tendinopathy, mainly in the lower limbs. A case-control study was designed to test for a relationship between certain collagen gene single nucleotide polymorphisms (SNPs) and elbow tendon pathology. A sample of 137 young adult athletes whose sports participation involves loading of the upper limb were examined for the presence of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
2
5
1
Order By: Relevance
“…These results are partly consistent with ours, where only the rs12722 polymorphism was associated with the joint dysfunction, while the female to male ratio was similar to our study. Mohmara et al obtained different findings regarding COL5A1 rs12722 and tennis elbow than those in Altinisik's and our study [27]. There was no significant relationship between rs12722 and lateral elbow tendinopathy, while SNP COL11A1 rs3753841 was associated with elbow tendon pathology.…”
Section: Discussioncontrasting
confidence: 79%
“…These results are partly consistent with ours, where only the rs12722 polymorphism was associated with the joint dysfunction, while the female to male ratio was similar to our study. Mohmara et al obtained different findings regarding COL5A1 rs12722 and tennis elbow than those in Altinisik's and our study [27]. There was no significant relationship between rs12722 and lateral elbow tendinopathy, while SNP COL11A1 rs3753841 was associated with elbow tendon pathology.…”
Section: Discussioncontrasting
confidence: 79%
“…33 Moreover, the DASH, the QuickDASH, and some custom simple questions (eg, did you, yes or no started-on pain provoking exercise/or physical activity) were only administered at 26 and 52 weeks’ follow-up. In the present study, most participants were middle-aged and overweight, 2,13 and only a few had sustained lateral elbow tendinopathy from sports activity, as reported in similar studies. 2,9,45…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, most participants were middle-aged and overweight, 2,13 and only a few had sustained lateral elbow tendinopathy from sports activity, as reported in similar studies. 2,9,45…”
Section: Discussionsupporting
confidence: 82%
“…Tendon cells possessing germline mutations or their derivatives (e.g., differentiated tenocytes) may not be suitable as donor cells for cell therapy. Examples include mutations or derivatives of COL5A1, MIR608 [134], TIMP2, MMP3 [135], TNC [136], DEFB1, FGFR1, FGF10 [137], CASP8 [138], GDF5 [139], FGF3, BMP4 [140], ESRRB [141], FCRL3 [142], SASH1, SAP30BP [143], rs71404070 located next to cadherin8 [144], COL11A1 [145], ADAMTS14 [146], ACAN, BGN, DCN, LUM-DCN [111], COL1A1 [147], COL12A1 [148], MMP12 [149], COL3A1 [150], VEGFA [151], FAM111B [152], COL5A3 [153], FBN2 [154] and SPARC [155]. Although the majority of these studies only revealed an association between genetic factors and tendon diseases, with some of them representing contradictory conclusions [150,156], our recent study on identification of a mutation of SPARC in patients with anterior cruciate ligament (ACL) and rotator cuff (RC) injuries [155] has suggested that use of autologous TDSC may not be suitable for treatment of these cohort of patients.…”
Section: Risk Predispositionmentioning
confidence: 99%